Factors associated with daily tenofovir exposure in Thai subjects taking combination antiretroviral therapy - Stephen J. Kerr (2018)
© Copyright 2015, Mary Ann Liebert, Inc. 2015. Tenofovir (TFV) exposure is associated with antiretroviral efficacy and risk of kidney disease. There is evidence of high interindividual variability of the pharmacokinetics of TFV. The effect of several clinical conditions on the pharmacokinetics of TFV has been observed and may partly explain its variability. We assessed factors influencing the pharmacokinetics of TFV in Thai patients. Thirty participants (50% female) taking efavirenz- or ritonavir-boosted protease inhibitor-based regimens were investigated. Intensive pharmacokinetic sampling was performed over 24 h. Multivariate geometric mean regression models adjusted for covariates with p≤0.2 in univariate analysis were developed. The median age was 41 years. Five participants [three taking a protease inhibitor (PI) and two taking efavirenz (EFV)] had mild renal dysfunction [estimated glomerular filtration rate (eGFR) 60-90 ml/min/1.73 m2; range 72-89]. TFV AUC0-24was 23% (95% CI 1-49%; p=0.04) higher in those taking PI vs. EFV, 39% (95% CI 5-84%; p=0.02) higher in those with mild renal dysfunction, and reduced by 16% (95% CI 5-26%; p=0.008) with each 10 kg body weight increase, after adjusting for sex and duration of TFV exposure. In PI-treated subjects TFV AUC0-24increased by 3% (0.3-6%; p=0.03) for each mg·h/liter increase in ritonavir (RTV) AUC0-24after adjusting for sex, weight, mild renal impairment, and proximal renal tubular dysfunction. Significantly higher TFV exposures were independently associated with PI regimens, mild renal impairment, lower body weight, and increasing RTV AUC0-24. Clinicians should be aware of the effect of these factors on TFV exposure when this drug is prescribed.